Derivation of governing equation for short-term shoreline response due to episodic storm wave incidence: comparative verification in terms of longshore sediment transport - Lim, Changbin; Lee, Jung-Lyul (Frontiers in Marine Science, 2023)
The shoreline temporarily recedes significantly as incoming storm waves reach the beach and cause wave breaking and energy dissipation. However, since the existing shoreline change model simulates shoreline change based on the longshore sediment transport rate (LSTR) empirical formulae, which are derived using the correlation between energy flux and littoral drift, it is difficult to simulate this phenomenon, which is drafted with transverse drift. Therefore, in this study, by applying the concept of the horizontal behavior of suspended sediments, a set of governing equations were derived that can simulate short-term shoreline changes in which the shoreline temporarily recedes, and then recovers. Among the three variables of the governing equation, the two main physical variables related to transverse drift—the beach response factor and the beach recovery factor—can be obtained from the median grain size. However, in the present study, the third variable, the actual transport speed of littoral drift, was estimated by comparison with the CERC formula and discussed from the point of view of alongshore energy flux and wave duration. This was established by introducing the delay factor of longshore sediment transport (DFLST), which indicates how slowly suspended sediments move relative to the longshore current speed. It was found that the littoral sediment speed is inversely proportional to the square root of the beach scale factor. The LSTR formula derived in this study was compared with the observed LSTR values collected from 25 beaches in the United States and with the results of four existing empirical formulae. The proposed governing equation is expected to be widely used as a means of predicting short-term shoreline changes, unlike existing shoreline change models, because it can consider the temporal shoreline retreat and recovery due to storm wave incidence.